Anne's House of Dreams - Montgomery, L. M.; Nang ChanYeema (New York, USA Bantam Books, 1998)
Anne marries Gilbert now a doctor. They move to Four Winds Harbor and new problems and surprises.
Keywords: Adult Fiction